Plantar sensation associates with gait instability in older adults - Jason R. Franz; Andrew D. Shelton; Kota Z. Takahashi; Jessica L. Allen (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Advanced age brings a loss of plantar sensation, represented, for example, as higher sensation thresholds in standardized testing. This is thought to contribute to an increased risk of falls among older adults – an intuitive premise that has yet to be fully investigated, especially in the context of walking balance. The purpose of this study was to quantify the association between plantar sensation and the instability elicited by a suite of walking balance perturbations that differ in direction and context in a cohort of n = 28 older adults (73.0 ± 5.9 yrs). Methods We measured plantar sensation using Semmes-Weinstein monofilaments and quantified margins of stability (MoS) and whole-body angular momentum (WBAM) during habitual walking and in response to optical flow perturbations, lateral waist-pull perturbations, and treadmill-induced slips. Results Our two major results were that higher monofilament thresholds (i.e., worse plantar sensation) in older adults associated with: (1) larger anterior-posterior (AP) and mediolateral (ML) MoS and increased transverse plane WBAM (p ≤ 0.031) during habitual walking, and (2) larger decreases in MoSAP, MoSML and larger increases in transverse plane WBAM in response to lateral waist pull perturbations (p ≤ 0.018). We found no associations between plantar sensation and responses to other perturbation contexts. Conclusions We conclude that there is an association between worse plantar sensation and gait instability, both during habitual unperturbed walking and in response to some perturbation contexts. These results should build confidence that interventions designed to improve plantar sensation for older adults, possibly through insoles or footwear modifications, could be critical for reducing gait-related falls in at-risk populations.